Modification of the B Ration for the Arctic and Desert - White, Virginia M (1984)
The availability of water for use by military personnel is critical in both desert and arctic environments. Menus and recipes developed for use under these conditions must meet the water requirements for troops, as well as provide items which are palatable and economical in terms of the amount of potable water needed for preparation. This report assess the impact of the arctic and desert environments on the Standard B Ration components and suggests menus, based on items in the B Ration, which address the need for a supply of adequate water to military personnel in both extremes of temperature, arctic and desert. The amount of water required for preparation of the food and beverages for 100 persons is given for both menus.